A comparative analysis of FDI in Turkey and the CEECs: Is there any link between FDI and trade? - Kosekahyaoglu, Levent (Journal of Business Economics and Management, 2006)
This paper examines the structure of foreign direct investment (FDI) flows into Turkey and the Central and Eastern European Countries (CEECs) as well as the other new members of the European Union (EU). Our study has two main parts. Firstly, we investigate the key economic and political factors that have an impact on foreign investment, for example, the macroeconomic performance, the production cost and the size of domestic market. Secondly, we explore the relationship between FDI and trade flows for Turkey, the Czech Republic, Hungary and Poland using the Granger causality methodology. Firstd Published Online: 14 Oct 2010